Perception of students about formation in the university through the ENADE student questionnaire (Research, Society and Development, 2021)
The objective of this research was to analyze the perception of students of the Chemistry course about their education, in addition to their conception of the course coordinator about the concept obtained in the National Student Performance Exam (ENADE). The data evaluated was carried out through the ENADE 2017 Student Questionnaire and the application of a questionnaire to students and the course coordinator on the possible factors that influenced the concept of the courses. The present research has a quantity-qualitative approach and descriptive. By analyzing the responses of the students to their perception of the concept of the course obtained in the ENADE 2017, we notice that these factors point out to factors such as: not enough time to answer the test, lack of student preparation, poor didactics by the professors, lack of interest in taking the test, lack of knowledge of the importance of evaluation, socioeconomic status and a protest, generated by the unsatisfaction experienced by the pioneer class of the course. The course coordinator states that he will make decisions about the grade obtained in the ENADE, however, he does not show interest in using the Student Questionnaire. It is possible to infer a great necessity for discussions about student dissatisfaction and divulgation of the ENADE. Based on the presented, we suggest the creation of an Evaluation Committee that, together with the coordination, that can work to disseminate and analyze the results of the ENADE and the Student Questionnaire.